Effects of age and hearing mechanism on spectral resolution in normal hearing and cochlear-implanted listeners - Horn, David L. (J Acoust Soc Am, 2017)
Spectral resolution limits speech perception with a cochlear implant (CI) in post-lingually deaf adults. However, the development of spectral resolution in pre-lingually deaf implanted children is not well understood. Acoustic spectral resolution was measured as a function of age (school-age versus adult) in CI and normal-hearing (NH) participants using spectral ripple discrimination (SRD). A 3-alternative forced-choice task was used to obtain SRD thresholds at five ripple depths. Effects of age and hearing method on SRD and spectral modulation transfer function (SMTF) slope (reflecting frequency resolution) and x-intercept (reflecting across-channel intensity resolution) were examined. Correlations between SRD, SMTF parameters, age, and speech perception in noise were studied. Better SRD in NH than CI participants was observed at all depths. SRD thresholds and SMTF slope correlated with speech perception in CI users. When adjusted for floor performance, x-intercept did not correlate with SMTF slope or speech perception. Age and x-intercept correlations were positive and significant in NH but not CI children suggesting that across-channel intensity resolution matures during school-age in NH children. No evidence for maturation of spectral resolution beyond early school-age in pre-lingually deaf implanted CI users was found in the present study.